Law No. 138 of 2021 Promulgating The Sovereign Sukuk Law = قانون رقم 138 لسنة 2021 بإصدار قنون الصكوك السيادية. (2025)
1. General provisions -- 2. Underlying assets for sukuk issuance -- 3. Sovereign securitization company -- 4. Supervisory committee -- 5. Association of sovereign sukuk owners -- Penalties.